Rap Poetry and Postmodernism - Molokov, Kirill; Zueva, Ekaterina (Journal of History Culture and Art Research, 2017)
This article observes several most significant rap albums of this decade within postmodern literature. Today rap culture ceased to be a sort of “outsider” in academic opinion, because of its influences on the culture and art innovations. We study albums as literary objects according to literary aesthetic theories and principles, display the main postmodern features they have, and analyze the role of rap poetry within postmodernism in general. The results suggest that rap poetry is postmodern not only musically, but also lyrically, as an object of literature. The rap music embodies all the postmodern traits and synthesizes them within the syntheses of music and literature and high art and pop culture.